Thank you for the opportunity to help you with your question!

Gradient of line perpendicular to the given line( p )= -(1/m)

where m is the gradient of the given line(i.e. y=3x-1) ; thus m=3

Therefore p=-(1/3)

Now the line with gradient -1/3 and passing through (0,-2) is

y-(-2)=-(1/3)(x-0)

y+2=-(1/3)x

y=-2-x/3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up